Hubungan Pola Makan dan Status Gizi pada Remaja Putri di Pondok Pesantren As’ad Kota Jambi - Aisah Aisah; Iin Indrawati; Siti Fati Hatussaadah (3031-8572, 2025)
Nutritional status is a determinant of everything related to development resources such as poor nutrition for children, especially children, so that it can reduce the potential of community development resources. Human resources are the Human Development Index (HDI) which has three main factors that are most important, namely, education, health and economy. These three factors are closely related to the nutritional status of the community. The prevalence of obesity in Jambi Province according to Riskesdas 2018 is 19.83%. The population in this study were 148 female adolescents at the Sa'ad Islamic Boarding School in Jambi City., with a sample size of 67 female studentsThe sample was selected using the Simple Random Sampling technique.This test is used to determine the relationship between the independent and dependent variables with a 95% significance level. If the p-value is ≤ 0.05, it indicates a significant relationship. This research was conducted from September 2024 to July 2025, the location of this research was the Sa'ad Islamic Boarding School, Jambi City.The results of the initial survey in August 2024 at the Sa'ad Islamic Boarding School through direct interviews with 10 young women, 7 of whom had symptoms of anemia such as lack of concentration while studying, fatigue, shortness of breath and a pale face. Knowing the Description of Eating Patterns with the Incident of Young Women at the Sa'ad Islamic Boarding School in Jambi City. The results showed that 45 respondents (52.2%) experienced malnutrition, while 32 respondents (47%) had good nutritional status. This indicates that there is a problem of malnutrition among young women at the AS'AD Islamic Boarding School in Jambi City. The description of eating patterns shows that respondents have a good diet, namely 7 female students (9%), while 71 (98%) respondents have a poor diet. The results of statistical tests using the Chi-square test showed a significant relationship between eating patterns and nutritional status in adolescents (p-value <0.05). This means that the worse a teenager's diet, the greater the likelihood of experiencing malnutrition. There is a problem of malnutrition among adolescent girls at the AS'AD Islamic Boarding School in Jambi City. The eating patterns of these adolescent girls are considered good.